Method for preparing high-strength formed activated carbon from high-water-content waste powdered activated carbon and product

By combining high-water waste powder activated carbon with mineral soil rinse agents, heating and stirring to form, the problems of difficult molding and poor bonding effect of high-water waste carbons are solved, and high-strength and high-temperature molded activated carbons are achieved, with significant results. cost advantages and market potential.

CN119488877APending Publication Date: 2025-02-21INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411591857.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

During the molding process, the high-water waste powder activated carbon has problems such as dry separation of materials during the extrusion process, and the inability to extrude, block the mold, and the bonding effect of the adhesive is generally poor in the prior art. , there are problems such as poor molding effect and large amount of adhesive use.

Method used

High-water waste powder activated carbon is used to combine it with mineral soil binder, reinforcement, plasticizer and body reinforcement, heat and stir evenly, mold and granulate, dry and roast, and screen to obtain high-strength molded activated carbon.

Benefits of technology

The high-efficiency molding of high-water waste powder activated carbon is achieved, the problem of difficulty in removing adsorbed water is solved, the strength and high-temperature resistance of the molded activated carbon are improved, the production process is simplified, and the energy consumption and binder use are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488877A_ABST
    Figure CN119488877A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-strength formed activated carbon from high-water-content waste powdery activated carbon and a product, and belongs to the technical field of activated carbon materials and environmental protection. The method comprises the following steps: by taking high-water-content waste powdery activated carbon as a raw material, compounding the high-water-content waste powdery activated carbon with a mineral soil adhesive, a reinforcing agent, a plasticizer and a green body reinforcing agent, heating and stirring, forming and granulating, drying and roasting, and screening to obtain formed activated carbon; the water content of the high-water-content waste powdery activated carbon is 45-65%, and the particle size is greater than or equal to 100 meshes; the mineral soil adhesive is a powder mixture of any one or two of kaolin and attapulgite, the particle size is greater than or equal to 100 meshes, and the viscosity is greater than or equal to 100 mPa.s. According to the method, the technical problems of dry-wet separation, mold blockage and the like caused by the existence of adsorbed water in the high-water-content waste powdery activated carbon in the extrusion granulation process are effectively solved, the particle strength and the ignition point of the formed activated carbon are remarkably improved, and the prepared formed activated carbon has the abrasive resistance larger than 97%, the ignition point larger than or equal to 400 DEG C and the carbon tetrachloride adsorption rate larger than or equal to 30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon materials and environmental protection, and specifically relates to a method for preparing high-strength shaped activated carbon by utilizing high-water-content waste powdered activated carbon and a product thereof. Background Art

[0002] Powdered activated carbon has the characteristics of large adsorption capacity, fast adsorption rate, strong decolorization ability, etc. It is suitable for decolorization and purification of high-pigment solutions such as chemical additives, dye intermediates, food additives, and pharmaceutical preparations, as well as deodorization and impurity removal of water pollutants. After being used for decolorization and water purification, powdered activated carbon will absorb a large amount of water when adsorbing adsorbents. The general water content is between 40% and 60%. This water combines with the adsorbent and is fixed in the pores of the activated carbon in the form of adsorbed water. Compared with free water, it is difficult to be effectively removed and utilized.

[0003] In the molding process of high-water-content waste powdered activated carbon, if the adsorbed water in the waste carbon is not removed in advance, during the molding and extrusion process, due to the effect of pressure, the adsorbate and adsorbed water in the waste carbon will quickly come out, resulting in dry and wet separation of the material (wet material comes out first, and the remaining dry material), and the dry material blocks the mold. It is still difficult to extrude even by increasing the pressure, and the mold is easily damaged. In order to solve the problem that the adsorbate and adsorbed water in high-water-content waste carbon are difficult to remove, an external heating method is usually used to heat and dry the high-water-content waste carbon, and then it is molded by adding water or a water-containing binder, which increases the production steps and consumes a lot of energy. At the same time, in the selection of molding binders, one or several binders are usually selected for use in combination, and there is a lack of research on methods for modifying the binder or improving the performance of the binder, resulting in generally poor bonding effects of the binder, poor molding effects of molded carbon, and large amounts of binders used. Directly molding high-water-content waste powdered activated carbon to prepare molded activated carbon can significantly increase the added value of waste carbon, and has great cost advantages and market potential. However, since current research has not made a breakthrough in the key molding technology in the production of high-water-content waste carbon, there are still problems such as difficulty in molding high-water-content waste carbon, poor molding effect, and low strength. Summary of the invention

[0004] One technical problem solved by the present invention is to provide a method for preparing high-strength shaped activated carbon using high-water-content waste powdered activated carbon, which solves the problems of dry-wet separation of materials during the extrusion process, inability to extrude, and mold clogging due to the presence of adsorbed water and adsorbates in the molding process of high-water-content waste powdered activated carbon; another technical problem to be solved by the present invention is to provide a high-strength shaped activated carbon, which uses high-water-content waste powdered activated carbon as raw material and has the characteristics of high strength and high temperature resistance.

[0005] Technical solution: In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon, comprising: using high-water-content waste powdered activated carbon as a raw material, compounding with a mineral soil binder, a reinforcing agent, a plasticizer, and a green body reinforcing agent, heating and stirring evenly, molding and granulating, drying and roasting, and screening to obtain high-strength molded activated carbon; the water content of the high-water-content waste powdered activated carbon is 45% to 65% (water adsorption), and the particle size is ≥100 mesh; the mineral soil binder is a powder mixture of any one of kaolin and attapulgite or both, with a particle size ≥100 mesh, a viscosity ≥100 mPa·s, and a moisture content ≤10%; preferably, the water content of the high-water-content waste powdered activated carbon is 45% to 60% (water adsorption), and the particle size is 100 mesh; the mineral soil binder is attapulgite, with a particle size of 100 mesh, a viscosity of 105 to 110 mPa·s, and a moisture content of 8% to 10%.

[0007] The method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon comprises the following components in parts by weight: 50-100 parts of high-water-content waste powdered activated carbon, 20-60 parts of mineral soil binder, 2-5 parts of reinforcing agent, 2-4 parts of plasticizer, and 0.2-0.5 parts of green body reinforcing agent; wherein the high-water-content waste powdered activated carbon and the mineral soil binder are calculated on a wet basis weight, and the reinforcing agent, the plasticizer and the green body reinforcing agent are calculated on a dry basis weight.

[0008] In the method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon, the reinforcing agent is a solid powder mixture of any one or both of magnesium hydroxide and magnesium oxide.

[0009] The method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon, wherein the plasticizer is a solid powder complex of polyvinyl alcohol and sodium carboxymethyl cellulose, and the mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose is 1:3.

[0010] In the method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon, the green body reinforcing agent is boric acid.

[0011] The method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon comprises the following components in parts by weight: 100 parts of high-water-content waste powdered activated carbon, 30-40 parts of mineral soil binder, 5 parts of reinforcing agent, 2-4 parts of plasticizer, and 0.5 parts of green body reinforcing agent.

[0012] The method for preparing high-strength shaped activated carbon using high-water-content waste powdered activated carbon has a calcination furnace heating rate of ≤20°C / min, a calcination temperature of 400-550°C, and a calcination time of 0.5-2h; preferably, the calcination furnace heating rate is 10°C / min, the calcination temperature is 450-500°C, and the calcination time is 0.5h.

[0013] The method for preparing high-strength shaped activated carbon using high-water-content waste powdered activated carbon comprises the following steps:

[0014] (1) Weigh high-water content waste powdered activated carbon, mineral soil binder, reinforcing agent, plasticizer, and green body reinforcing agent, add them into a mixer, and heat and stir evenly;

[0015] (2) The pH value of the mixed material after mixing is ≥9, and the mixture is stirred for 30 minutes. After the stirring is completed, the mixture is taken out and transferred to a molding machine for granulation to form granules; preferably, the pH value of the mixed material after mixing is 9.0-10.0.

[0016] (3) After the particles are dried, they are placed in a calcining furnace for calcination. After all the steps are completed, the product is taken out and sieved to obtain high-strength activated carbon.

[0017] In the method for preparing high-strength molded activated carbon using high-water-content waste powdered activated carbon, the material temperature is maintained at 70-80°C during the hot stirring process, preferably at 75°C.

[0018] The high-strength shaped activated carbon prepared by the above method.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0020] (1) The method of the present invention can form and granulate without adding water, is simple to operate, easy to implement, and has the characteristics of being economical and environmentally friendly. The mineral soil binder, reinforcing agent, plasticizer, and green body reinforcing agent used are low in price and widely available, and have obvious cost advantages.

[0021] (2) The present invention uses a highly water-absorbent mineral soil binder (there are a large number of hydrogen bonds and electrostatic forces in the crystal structure, and the water content is ≤10%) and a plasticizer (containing a large number of hydrophilic groups), and heats and stirs to achieve the removal and absorption of adsorbed water in waste powdered activated carbon. Both the mineral soil binder and the plasticizer have high water absorption and can absorb 100% of their own weight of water. The heating during the stirring process can stimulate the excitation of electrons in the adsorbed water molecules, change the activation energy of the reaction, and thus give them enough energy to break free from the constraints of the activated carbon, thereby combining with materials such as binders and plasticizers. By using highly water-absorbent binders, plasticizers, heating and stirring and other technical means, the problems of dry-wet separation of materials and mold clogging during the molding process caused by the difficulty of adsorbed water combining with materials are solved, and efficient molding of waste powdered activated carbon with high water content is achieved.

[0022] (3) In order to improve the strength of the molded activated carbon, the present invention stipulates the viscosity and particle size of the mineral soil binder. Mineral clay has a good aspect ratio and abundant internal pores. It is not only a good adsorption material but also has a flame retardant effect. The use of the mineral soil binder can ensure that the binder has a certain initial adhesion and sustained adhesion. The viscosity and moisture of the mineral soil binder will affect the initial strength, water absorption and plasticity of the molding material. The mineral soil binder with high viscosity and low moisture is more suitable for molding. The molding process can not only reduce the material loss rate, but also improve the molding efficiency.

[0023] The metal elements in the reinforcing agent can form a stable hydrate binder with dissolved silicon dioxide under water and a certain pH value, enhancing the bonding ability of inorganic mineral clay. In addition, the reinforcing agent also plays a role in adjusting the alkalinity of waste powdered activated carbon and increasing the binding force between waste powdered activated carbon and inorganic mineral clay. At the same time, the introduction of metal cations in the reinforcing agent can coordinate with water molecules to form hydrogen bonds, thereby enhancing the stability of the structure;

[0024] The addition of plasticizers can increase the plasticity and flexibility of materials, reduce the formation of stress in extruded materials, and make the molding process smoother. Polyvinyl alcohol and sodium carboxymethyl cellulose can be used together to form a blended film (the metal cations in the particle enhancer can promote its cross-linking). After wrapping the material, the mechanical properties are enhanced, so that the molding strength of the material can be improved. At the same time, the plasticizer has a certain adhesive force and water retention after absorbing water, which can significantly improve the molding strength;

[0025] The main function of boric acid as a green body reinforcing agent is to reduce the cracking of materials during extrusion molding and roasting. It can reduce the surface tension of materials and reduce thermal expansion, thereby preventing cracking and falling off of materials. In addition, for plasticizers containing hydroxyl molecules, boric acid can also act as a cross-linking agent to increase the water resistance and stability of plasticizers.

[0026] (4) The molded activated carbon prepared by the present invention has the characteristics of good molding effect, high strength, high temperature resistance, etc., and is mainly used in the field of gas phase adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the appearance of high-strength molded activated carbon. DETAILED DESCRIPTION

[0028] The present invention is further illustrated below in conjunction with specific examples and comparative examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0029] The plasticizer used in the following examples is a solid powder complex of polyvinyl alcohol and sodium carboxymethyl cellulose. In order to enhance the mechanical properties and generate a blended film, the mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose is 1:3.

[0030] Example 1

[0031] A method for preparing high-strength shaped activated carbon using high-water-content waste powdered activated carbon, comprising the following steps:

[0032] (1) Weigh 100 g of waste powdered activated carbon (water content 60%, particle size passing 100 mesh sieve), 30 g of attapulgite (viscosity 110 mPa·s, particle size passing 100 mesh sieve, water content 10%), 5 g of magnesium hydroxide, 4 g of plasticizer, and 0.5 g of boric acid, and mix them;

[0033] (2) Stirring evenly in a 75°C heating mixer, the pH value of the mixture is 10, and the stirring time is 30 minutes. After the stirring is completed, the mixture is taken out and transferred to a hydraulic molding machine (pressure 15 tons) to granulate into columnar particles;

[0034] (3) After drying the particles in an oven at 100°C, the particles are placed in a calcining furnace and calcined at a heating rate of 10°C / min, a calcination temperature of 450°C, and a calcination time of 0.5 h. After all steps are completed, the product is taken out and sieved to obtain the finished activated carbon.

[0035] The activated carbon product is in granular shape, with a smooth surface and no cracks, abrasion resistance (GB / T 12496.6-1999) of 99%, ignition point (GB / T 20450-2006) of 413°C, and carbon tetrachloride adsorption rate (GB / T 12496.5-1999) of 45%.

[0036] Example 2

[0037] A method for preparing high-strength shaped activated carbon using high-water-content waste powdered activated carbon, comprising the following steps:

[0038] (1) Weigh 100 g of waste powdered activated carbon (water content 45%, particle size passing 100 mesh sieve), 40 g of attapulgite (viscosity 105 mPa·s, particle size passing 100 mesh sieve, water content 8%), 5 g of magnesium oxide, 2 g of plasticizer, and 0.5 g of boric acid, and mix them;

[0039] (2) Stirring the mixture in a 75°C heating mixer to obtain a uniform mixture with a pH value of 9.0 for 30 min. After stirring, the mixture is taken out and transferred to a hydraulic molding machine (pressure 15 tons) to form columnar particles.

[0040] (3) After drying the particles in an oven at 100°C, the particles are placed in a calcining furnace and calcined at a heating rate of 10°C / min, a calcination temperature of 500°C, and a calcination time of 0.5h. After all steps are completed, the product is taken out and sieved to obtain the finished activated carbon.

[0041] The activated carbon product is in granular shape, with a smooth surface and no cracks, abrasion resistance (GB / T 12496.6-1999) of 100%, ignition point (GB / T 20450-2006) of 434°C, and carbon tetrachloride adsorption rate (GB / T 12496.5-1999) of 34%.

[0042] Example 3

[0043] A method for preparing high-strength shaped activated carbon using high-water-content waste powdered activated carbon, comprising the following steps:

[0044] (1) Weigh 100 g of waste powdered activated carbon (water content 50%, particle size passing 100 mesh sieve), 30 g of attapulgite (viscosity 105 mPa·s, particle size passing 100 mesh sieve, water content 10%), 5 g of magnesium hydroxide, 4 g of plasticizer, and 0.5 g of boric acid, and mix them;

[0045] (2) Stirring evenly in a 75°C heating mixer, the pH value of the mixture was 9.6, and the stirring time was 30 min. After the stirring was completed, the mixture was taken out and transferred to a ring die granulation molding machine (compression ratio 1:1.5) to granulate into columnar particles;

[0046] (3) After drying the particles in an oven at 100°C, the particles are placed in a calcining furnace and calcined at a heating rate of 10°C / min, a calcination temperature of 450°C, and a calcination time of 0.5 h. After all steps are completed, the product is taken out and sieved to obtain the finished activated carbon.

[0047] The activated carbon product is in granular shape, with a smooth surface and no cracks, abrasion resistance (GB / T 12496.6-1999) of 97%, ignition point (GB / T 20450-2006) of 407°C, and carbon tetrachloride adsorption rate (GB / T 12496.5-1999) of 39%.

[0048] Comparative Example 1

[0049] (1) Weigh 100 g of waste powdered activated carbon (water content 60%, particle size passing 100 mesh sieve), 30 g of attapulgite (viscosity 80 mPa·s, particle size passing 100 mesh sieve, water content 20%), 5 g of magnesium hydroxide, 4 g of plasticizer, and 0.5 g of boric acid, and mix them;

[0050] (2) Stirring evenly in a 75°C heating mixer, the pH value of the mixture is 8.7, the stirring time is 30 minutes, and after the stirring is completed, the mixture is taken out and transferred to a hydraulic molding machine (pressure 15 tons) to granulate into columnar particles;

[0051] (3) During the molding process, the material is separated into dry and wet parts. One part is easily squeezed out without any strength; the other part blocks the mold and cannot be squeezed out, resulting in huge waste of material.

[0052] Comparative Example 2

[0053] (1) Weigh 100 g of waste powdered activated carbon (water content 60%, particle size passing 100 mesh sieve), 30 g of attapulgite (viscosity 110 mPa·s, particle size passing 100 mesh sieve, water content 10%), and 4 g of plasticizer, and mix them;

[0054] (2) Stirring evenly in a 75°C heating mixer, the pH value of the mixture is 8.0, the stirring time is 30 minutes, and after the stirring is completed, the mixture is taken out and transferred to a hydraulic molding machine (pressure 15 tons) to granulate into columnar particles;

[0055] (3) After drying the particles in an oven at 100°C, the particles are placed in a calcining furnace and calcined at a heating rate of 10°C / min, a calcination temperature of 450°C, and a calcination time of 0.5 h. After all steps are completed, the product is taken out and sieved to obtain the finished activated carbon.

[0056] The activated carbon product is in granular shape with a smooth surface and a small amount of cracking. The abrasion resistance (GB / T 12496.6-1999) is 89%, the ignition point (GB / T 20450-2006) is 401°C, and the carbon tetrachloride adsorption rate (GB / T 12496.5-1999) is 46%.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon, characterized in that: High-water-content waste powdered activated carbon is used as raw material, compounded with mineral soil binder, reinforcing agent, plasticizer, and green body reinforcing agent, heated and stirred evenly, formed into granules, dried and roasted, and sieved to obtain high-strength formed activated carbon; the water content of the high-water-content waste powdered activated carbon is 45% to 65%, and the particle size is ≥100 mesh; the mineral soil binder is a powder mixture of any one of kaolin and attapulgite or two, with a particle size ≥100 mesh, a viscosity ≥100 mPa·s, and a moisture content ≤10%.

2. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 50-100 parts of high-water-content waste powdered activated carbon, 20-60 parts of mineral soil binder, 2-5 parts of reinforcing agent, 2-4 parts of plasticizer and 0.2-0.5 parts of green body reinforcing agent.

3. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The reinforcing agent is a solid powder mixture of any one of magnesium hydroxide and magnesium oxide or both.

4. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The plasticizer is a solid powder complex of polyvinyl alcohol and sodium carboxymethyl cellulose, and the mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose is 1:

3.

5. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The green body reinforcing agent is boric acid.

6. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 100 parts of high-water-content waste powdered activated carbon, 30-40 parts of mineral soil binder, 5 parts of reinforcing agent, 2-4 parts of plasticizer and 0.5 part of green body reinforcing agent.

7. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The heating rate of the roasting furnace is ≤20℃ / min, the roasting temperature is 400~550℃, and the roasting time is 0.5~2h.

8. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The following steps are involved: (1) Weigh high-water content waste powdered activated carbon, mineral soil binder, reinforcing agent, plasticizer, and green body reinforcing agent, add them into a mixer, and heat and stir evenly; (2) After mixing, the mixture has a pH of ≥9, and is stirred for 30 min. After the stirring is completed, the mixture is taken out and transferred to a molding machine for granulation into granules; (3) After the particles are dried, they are placed in a calcining furnace for calcination. After all the steps are completed, the product is taken out and sieved to obtain high-strength activated carbon.

9. The method for preparing high-strength shaped activated carbon using high-water content waste powdered activated carbon according to claim 1, characterized in that: The material temperature was maintained at 70-80°C during the hot stirring process.

10. High-strength shaped activated carbon prepared by the method according to any one of claims 1 to 9.